A Continuum of Pedagogies for Preparing Teachers to Use High-Leverage Practices. (November 2019) - Brownell, Mary T.; Benedict, Amber E.; Leko, Melinda M.; Peyton, David; Pua, Daisy; Richards-Tutor, Catherine
This article provides a framework and description of pedagogies that may be used in teacher preparation across a range of settings from college classrooms to P-12 settings to support teacher candidates as they learn to use high-leverage practices (HLPs). These "pedagogies of enactment" must include a continuum of opportunities to use teaching practices in increasingly authentic settings, ranging from video analysis, case studies, rehearsal, and virtual simulations to use of practices with coaching support in a classroom (e.g., lesson study, structured tutoring, and aligned field experiences). In this article, we use research on the development of professional expertise and from cognitive science to identify pedagogies from the teacher education research base that have promise for promoting candidates' learning and describe how these pedagogies might be scaffolded over the duration of a teacher education program to promote learning.